NEW TARGET MICROVESICLES AND EXOSOMES IN CANCER - Sema Bolkent (İstanbul Tıp Fakültesi Dergisi)
In recent years, a new mechanism for intercellular communication has been put forward which involves the intercellular transfer of extracellular vesicles. Most cancer cells release potentially functional biomolecules loaded in extracellular vesicles (EVs) such as DNA, proteins, lipids, and microRNAs. The experiments showed that EVs uptake by tumor cells can alter cellular behavior. Exosomes, a subtype of EVs, are small, lipid bilayer membrane vesicles for intercellular communication. Exosomes communicate with near-by and distant cancer cells that promote cancer development, metastasis, and drug resistance. In addition to intercellular communication, exosomes play a role in many biological processes such as signal transmission, genetic material transfer, and regulation of the immune response. EVs have emerged as an alternative mediator of communication within the tumor microenvironment and cancer metastasis. Because exosomes can change their content during various cancer treatments, they can play an important role in following the treatment. This review focuses on the function of EVs as signal transmitters between cells, called communicasomes (intercellular communication), and the importance of this function in cancer diagnosis and treatment.